Ceftaroline Increases Membrane Binding and Enhances the Activity of Daptomycin against Daptomycin-Nonsusceptible Vancomycin-Intermediate Staphylococcus aureus in a Pharmacokinetic/Pharmacodynamic Model - Werth, Brian J. (American Society for Microbiology, 2013)
New antimicrobial agents and novel combination therapies are needed to treat serious infections caused by methicillin-resistant Staphylococcus aureus (MRSA) with reduced susceptibility to daptomycin and vancomycin. The purpose of this study was to evaluate the combination of ceftaroline plus daptomycin or vancomycin in an in vitro pharmacokinetic/pharmacodynamic model. Simulations of ceftaroline-fosamil at 600 mg per kg of body weight every 8 h (q8h) (maximum free-drug concentration in serum [fC(max)], 15.2 mg/liter; half-life [t(1/2)], 2.3 h), daptomycin at 10 mg/kg/day (fC(max), 11.3 mg/liter; t(1/2), 8 h), vancomycin at 2 g q12h (fC(max), 30 mg/liter; t(1/2), 6 h), ceftaroline plus daptomycin, and ceftaroline plus vancomycin were evaluated against a clinical, isogenic MRSA strain pair: D592 (daptomycin susceptible and heterogeneous vancomycin intermediate) and D712 (daptomycin nonsusceptible and vancomycin intermediate) in a one-compartment in vitro pharmacokinetic/pharmacodynamic model over 96 h. Therapeutic enhancement of combinations was defined as ≥2 log(10) CFU/ml reduction over the most active single agent. The effect of ceftaroline on the membrane charge, cell wall thickness, susceptibility to killing by the human cathelicidin LL37, and daptomycin binding were evaluated. Therapeutic enhancement was observed with daptomycin plus ceftaroline in both strains and vancomycin plus ceftaroline against D592. Ceftaroline exposure enhanced daptomycin-induced depolarization (81.7% versus 72.3%; P = 0.03) and killing by cathelicidin LL37 (P < 0.01) and reduced cell wall thickness (P < 0.001). Fluorescence-labeled daptomycin was bound over 7-fold more in ceftaroline-exposed cells. Whole-genome sequencing and mutation analysis of these strains indicated that change in daptomycin susceptibility is related to an fmtC (mprF) mutation. The combination of daptomycin plus ceftaroline appears to be potent, with rapid and sustained bactericidal activity against both daptomycin-susceptible and -nonsusceptible strains of MRSA.